Frequency of Helicobacter pylori (H. pylori) in Patients Operated for Duodenal Ulcer Perforation - Khan, Bilal Irshad; Waris, Hira; Amir, Asad; Nazir, Amna; Khan, Atif; Ali, Qasim (Biological and Clinical Sciences Research Journal, 2025)
Helicobacter pylori infection is a well-recognized cause of peptic ulcer disease and may contribute to serious complications such as duodenal ulcer perforation. The burden of H. pylori–associated perforation varies across populations and remains clinically relevant in developing countries. Objective: To determine the prevalence of Helicobacter pylori infection among patients presenting with duodenal ulcer perforation. Methods: A descriptive cross-sectional study was conducted in the Department of Surgery, Holy Family Hospital, Rawalpindi, from April 2025 to June 2025. A total of 94 patients aged 18–70 years presenting with acute abdominal pain and confirmed duodenal ulcer perforation were enrolled, irrespective of gender. Patients with malignant or traumatic perforation, frequent use of salicylates or non-steroidal anti-inflammatory drugs in the preceding six months, pregnancy or lactation, recurrent gastric complications, ongoing antibiotic therapy, circulatory failure (systolic blood pressure <90 mmHg and diastolic blood pressure <60 mmHg), HIV infection, or other immunosuppressive conditions were excluded. Helicobacter pylori infection was assessed using the carbon-labeled urea breath test. A delta value ≥4.0% above baseline after 30 minutes was considered a positive result. Data were analyzed using SPSS, and descriptive statistics were calculated for demographic and clinical variables. Results: The mean age of the participants was 45.07 ± 10.67 years (range 18–70 years). Most patients (54.26%) were aged 46-70 years. There was a male predominance, with 58 males (61.70%) and 36 females (38.30%), resulting in a male-to-female ratio of 1.6:1. Helicobacter pylori infection was detected in 36 patients (38.30%) who underwent surgery for duodenal ulcer perforation. Conclusion: Helicobacter pylori infection was identified in a considerable proportion of patients presenting with duodenal ulcer perforation. The findings suggest that H. pylori may contribute to the occurrence of perforated peptic ulcer disease in the local population, highlighting the importance of screening and eradication strategies.